1995
DOI: 10.1002/macp.1995.021961110
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of poly(p‐phenylene) based nonlinear optical materials

Abstract: This paper describes preliminary work exploring the feasibility of preparing high-performance nonlinear optical (NLO) materials based on the poly@-phenylene (PPP) backbone. Three new monomer/NLO-phores of the general formula: 4-RS0,C,H4C= C(4-XC6HS (where R = 2,5-dichlorophenyl; 2a, X = H; 2b, X = OCH,; 2c, X = N(CH,)d were synthesized and then homopolymerized using catalytic nickel and stoichiometric zinc to produce the poly@-phenylenes), 3 a-c, respectively, as lowmolecular-weight materials (number-average m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Several attempts at polymerizing compounds 1a-1c were made using nickel-catalysis and stoichiometric zinc. We have previously shown that 2,5-dichlorosulfonyl monomers do nicely polymerize under these conditions [15]; however, for each of the monomers prepared in this study we were unable to isolate a poly-p-phenylene product for further analysis. Tables 2 and 3 list the isopleths, solution densities, and the type of transitions for PDBS-CO 2 and FPDBS-CO 2 mixtures investigated in this study from approximately room temperature to 100 8C.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Several attempts at polymerizing compounds 1a-1c were made using nickel-catalysis and stoichiometric zinc. We have previously shown that 2,5-dichlorosulfonyl monomers do nicely polymerize under these conditions [15]; however, for each of the monomers prepared in this study we were unable to isolate a poly-p-phenylene product for further analysis. Tables 2 and 3 list the isopleths, solution densities, and the type of transitions for PDBS-CO 2 and FPDBS-CO 2 mixtures investigated in this study from approximately room temperature to 100 8C.…”
Section: Resultsmentioning
confidence: 84%
“…Chemical synthesis and molecular structure Phenyl 2,5-dichlorobenzenesulfonate (PDBS) [14] and pentafluorophenyl 2,5-dichlorobenzenesulfonate (FPDBS) are prepared in high yield from the inexpensive and commercially available 2,5-dichlorobenzenesulfonyl chloride, which has proven a valuable synthetic launching point for several poly ( p-phenylene) monomer syntheses prior to this work [15].…”
Section: Resultsmentioning
confidence: 99%
“…The crude solids were left to air-dry overnight before drying in a vacuum oven until a constant weight measurement was obtained (18.67 g, 45% yield); mp 132.2°C (DSC). 1 Polymerization. Ni(0) coupling chemistry was used to polymerize the rigorously purified monomer.…”
Section: Methodsmentioning
confidence: 99%
“…The crude solids were left to air-dry overnight before drying in a vacuum oven until a constant weight measurement was obtained (18.67 g, 45% yield); mp 132.2 °C (DSC). 1 H NMR (CDCl3): σ (ppm) 8.00 (s,1,-CONHAr) 7.90 (s, 1, aromatic-H) 7.78 (d,1, ortho aromatic -H of anilide) 7.54 (t,1, meta aromatic -H of anilide) 7.40 (s, 2, aromatic-H) 7.34 (t,1, para aromatic-H of anilide). 13 Preparation of 4′-(N,N-Diethylamino)-2,5-dichlorobenzophenone (2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation